Evaluasi Kinerja Pengelolaan Pendapatan Daerah Berdasarkan Perspektif Performance Management di Kabupaten Sigi - Risqi Amalia; Norlin Terontja; Fajriyatul Putri; Nina Yusnita Yamin; Betty Betty; Andi Chairil Furqan (Journal of Innovative and Creativity, 2026)
Fiscal decentralization in Indonesia has mandated local governments to enhance their fiscal autonomy through optimization of Local Own-Source Revenue (Pendapatan Asli Daerah/PAD). However, the implementation of performance management systems in revenue management remains nascent and insufficiently integrated into strategic decision-making processes. This study evaluates the performance of revenue management at Sigi Regency during 2022–2024 through a performance management lens, utilizing a descriptive quantitative approach. The research analyzes three key indicators: revenue effectiveness ratios, year-on-year growth rates, and PAD contribution to total regional revenue, based on official financial reports from the Regional Revenue Agency (Bapenda). Findings demonstrate that Sigi Regency achieved positive quantitative results: effectiveness ratios ranging from 97.96% to 124.29%, average revenue growth of 20.07% annually (exceeding national benchmark of 8–10%), and consistent upward trends in revenue realization. However, evaluation through the performance management framework reveals output-oriented rather than process and learning-oriented implementation, as evidenced by: (1) relatively low PAD contribution to total revenue (indicating persistent dependency on central government transfers of 60–85%), (2) unoptimized integration of performance information into strategic decision-making, and (3) incomplete revenue diversification strategy. This study concludes that while Kabupaten Sigi demonstrates commendable financial performance quantitatively, strengthening the performance management cycle particularly in performance information utilization, managerial capacity building, and development of long-term fiscal independence strategies remains essential for sustainable revenue management improvements.